Компенсація паразитної ємності дроселя для електромережних протизавадних фільтрів - Павловський, Володимир Олександрович; Юрченко, Олег Миколайович (НТУ "ХПІ", 2017)
У статті розглянуто спосіб компенсації паразитної ємності дроселя для електромережних протизавадних фільтрів. Одержано вирази для оптимального значення ємності конденсатора у схемі компенсації в залежності від ступеню магнітного зв’язку між обмотками дроселя схеми компенсації та від граничної частоти. Результати електронного моделювання підтвердили правильність одержаних виразів.

The article considers a method for compensation of the parasitic capacitance of the throttle for electric network noise suppression filters. Expressions are obtained for the optimum capacitor capacitance in the compensation circuit, depending on the degree of magnetic coupling between the throttle windings, the compensation circuit, and the limiting frequency. The results of the electronic simulation confirmed the correctness of the expressions obtained.
Compensation of the parasitic capacitance of the throttle for power grid interference suppression filters
Keywords: електромагнітна сумісність; котушка індуктивності; конденсатор; індуктивний зв'язок; parasitic capacitance of throttle; interference suppression filter; electromagnetic compatibility